Curation contents as a core competency in MOOC learning among students using engagement theory framework / Nik Rozilaini Wan Mohamed and Dziauddin Sharif - Wan Mohamed, Nik Rozilaini; Sharif, Dziauddin (Academy of Contemporary Islamic Studies (ACIS), 2021)
The purpose of this paper to identify the curation contents effectiveness on online distance learning and to envision the requirements of the future generation of students on new ways on delivering the knowledge. The objective of this research is to distinguish the curation activity by assembly “knowledge presentations” in a Massive Open Online Courses (MOOCs) courses offered by Universiti Teknologi MARA, Malaysia. The major factor analysis of curator’s activities resulted in three factors based on engagement theory related with students work in a collaborative team, students work to develop skills and find a solution to a problem through use of curators’ presentation and students make a valuable contribution to the team whilst learning, creating an authentic learning experience where skills learned can be 'adapted' to real life. The theory was adapted from engagement theory with for constructs; behaviour engagement, cognitive engagement, emotional engagement, and agentic engagement that reflect the students’ academic achievement. The survey will be distributed to 86 Diploma students from UiTM evaluated one subject HTT167 under Massive Open Online Course (MOOCs), the quantitative will be conducted for the analysis using PLS SEM (Partial Least Squares Structural Equation Modelling) to analyse the data. The proposed study will a taxonomy of components that are included in the curation process, to increase students’ engagements in learning. The curation contents contribute to the students make a valuable contribution to the students’ teams whilst learning, creating an authentic learning experience where skills learned can be 'adapted' to real life problems that assist students to make decisions in their daily lives. The finding will improve the 21st century students’ knowledge and skills which requires personal and social skills, e.g., cognitive, and meta-cognitive skills from an individual and social perspective.